POLÍTICAPP: HACIA UNA CATEGORIZACIÓN DE LAS APPS MÓVILES DE COMUNICACIÓN POLÍTICA - Dr. Pablo VÁZQUEZ SANDE (Fonseca, Journal of Communication, 2023)
This article is an analyze of all mobile apps that are available in the field of Spanish political communication, with the aim to develop a pioneering categorization of these platforms according to various criteria as promoters, aims pursued or areas of performance. It includes also a critical review from which it is concluded that these app reproduce classic communication patterns with the voters. That means that the implementation of these channels seems to have been due more to political marketing than to boost democratic participation or to introduce an horizontal outline of a new relationship between politicians and citizens